LOCAL WISDOM OF ELECTRIC CARD AS A COACHING MEDIA FOR THE COMMUNITY OF PESANGGARAN DISTRICT, BANYUWANGI REGENCY - Tofan Priananda Adinata; Desy Sulistiana Ardiyani (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study aims to determine the causes and objectives of people who still believe and visit shamans as a shortcut to solving a problem, especially in Pesanggaran District. The discussion studied in this study is 1) What are the causes and objectives that underlie the community still believing in shamans as helpers in solving their problems?, 2) How does the Lintrik Card as a coaching media influence the behavior of people who still believe in Lintrik in solving their problems? From the results of the study, it was found that people who still believe in and visit shamans in Pesanggaran District are due to causal factors and objectives. The causes of people who still believe in and visit shamans in Pesanggaran District are due to the influence of the community's environment and culture, as well as the lack of instilling religious values and norms. Where the actions of these communities will have an influence on community behavior both in decision-making and daily actions. The research method used in this study uses cultural anthropology research. In general, researchers concluded that people who still believe in and visit lintrik shamans in Pesanggaran District do so based on the causes and goals that influence their actions. These actions, in turn, influence the behavior of those who use lintrik.